Structural designing of suppressors for autisms spectrum diseases using molecular dynamics sketch - Bipin Nair BJ; Vijesh Bhaskaran; Arunjit K (International Journal of Drug Delivery, 2016)
In this paper we are sketching the chemical structure of suppressor drug for autism spectrum disorder using a computational tool .Here we are designing three molecular compounds like Fluoxetine, Risperidone, Melatonin .Structuring the suppressors, sketching the aromatization and bonding of the functional groups withthe elements like Oxygen ,Nitrogen ,halogens. In our work we are using computational algorithm for drawing the structure of suppressor drug. In this paper we are mentioning the autism spectrum suppressor’s molecular formula as well as structural formula.